2012
DOI: 10.1590/s0066-782x2012005000031
|View full text |Cite
|
Sign up to set email alerts
|

Realce Tardio miocárdico por Ressonância Magnética Cardíaca pode identificar risco para Taquicardia Ventricular na Cardiopatia Chagásica Crônica

Abstract: Background: Invasive and non-invasive tests have been used to identify the risk of ventricular tachycardia (VT) in patients with chagas' cardiomyopathy (CCM). Cardiac magnetic resonance imaging (CMRI) using the delayed enhancement (DE) technique can be useful to select patients with global or segmentary ventricular dysfunction, with high degree of fibrosis and at higher risk for clinical VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…Recently, Regueiro et al 18 , in a descriptive study, have shown the association of ECG changes (with segmental wall motion abnormality) with the increase in fibrosis mass and right and left ventricular dysfunctions. Mello et al 19 , assessing patients with CCHD on CMR, have shown that transmural fibrosis in more than two LV myocardial segments was more often associated with ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Regueiro et al 18 , in a descriptive study, have shown the association of ECG changes (with segmental wall motion abnormality) with the increase in fibrosis mass and right and left ventricular dysfunctions. Mello et al 19 , assessing patients with CCHD on CMR, have shown that transmural fibrosis in more than two LV myocardial segments was more often associated with ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…[101103] CMRI, using the delayed enhancement technique, can be useful to select patients with global or regional ventricular dysfunction, with high degree of fibrosis and at higher risk for clinical VT.[103] The presence of zones of slow conduction in the myocardium may be recognized by the presence of prolonged filtered QRS duration obtained by signal averaged ECG, which was shown to be an independent predictor of death in Chagas disease patients. [101] Since both CMRI and signal-averaged ECG are not readily available, an alternative simple, noninvasive method is a 12-lead ECG QRS scoring system, which quantifies myocardial fibrosis, correlates with the scar, evaluated by CMRI, and with LV dysfunction and with malignant VT.[102]…”
Section: Electrocardiology Of Ventricular Arrhythmiasmentioning
confidence: 99%
“…Each 1% increment in LGE extent was independently associated with arrhythmic outcome (HR 1.10, 95% CI 1.05–1.16; P  < 0.001)Neilan et al33 162NA(infiltrative cardiomyopathy excluded)Presence of LGEExtent of LGEPresence of LGE (HR 14, 95% CI 4.4-45.6; p<0.001) and each 1% increment in LGE extent (HR 1.17, 95% CI 1.12–1.22; P  < 0.0001) were strongly associated with appropriate ICD therapy or non-heart failure cardiac deathMasci et al34 228DCMChemotherapy (n=7)Presence of LGEPatients with LGE showed 8.3-fold higher risk of aborted SCD versus patients without LGE (95% CI 1.66–41.55; P  = 0.01)Grün et al35 222MyocarditisPresence of LGEExtent of LGELGE was more frequently observed among patients who presented with SCD compared with patients without event (100% vs 43%; P  < 0.001). Presence of LGE was independently associated with cardiac death (HR 12.8; P  < 0.01)Mello et al36 41Chagas cardiomyopathyPresence of LGEExtent of LGEThe presence of ≥2 LV segments with transmural scar was independently associated with ventricular arrhythmias (relative risk 4.1; 95% CI 1.06–15.68; P  = 0.04)Kramer et al37 57Anderson-Fabry’s diseasePresence of LGEProgression of LGEOnly patients with LGE presented with ventricular arrhythmic events. Annual increase in fibrosis (LGE) was the only independent predictor of ventricular arrhythmias ( P  = 0.038)Florian et al38 88Duchnne and Becker muscular dystrophiesPresence of LGEPresence of transmural LGE was independently associated with heart failure hospitalizations or ventricular arrhythmias (HR 2.89, 95% CI 1.09–7.68; P  = 0.033)Greulich et al39 155SarcoidosisPresence of LGEPatients with LGE had 31.6-fold increased risk of presenting with death, aborted SCD, or appropriate ICD therapy ( P  = 0.0014)Murtagh et al40 205SarcoidosisPresence of LGEExtent of LGEThe annualized rate of death or ventricular tachycardia was significantly higher among patients with LGE compared with patients without (4.93% vs 0.24%, P  < 0...…”
Section: Introductionmentioning
confidence: 93%